Gambaran Paparan Gas Buang Kendaraan (Pb) dengan Kadar Hemoglobin dan Eritrosit Berdasarkan Lama Kerja Pada Petugas Operator Wanita SPBU - Mifbakhuddin Mifbakhuddin; Puji Mumpuni; Wulandari Meikawati (Poltekkes Kemenkes Yogyakarta, 2011)
The growing number of vehicles in Semarang city has great potentiality toward air pollution that will affecting people’s health. The health impact of lead ex-posure may in the forms of hypertension, anaemia, brain function degradation, and red cell formation inhibition. The study was aimed to understand the correlation between lead level in blood and haemoglobin and erythrocytes based on working time duration among female operators of gas stations located in South Semarang. The study employed cross sectional design and consisted of 30 sample. The independent variables are blood lead concen-tration and working time duration, while the dependent variables are haemo-globin and erythrocytes. Pearson Correlation Product Moment was used as the statistical test. Descriptively, the results showed that most of the operators had been worked just for 5 months, had blood lead exceeding the threshold of 20 µg/dl, and had normal haemoglobin and erythrocites. However, the study found that there was no significant correlation between working time duration and blood lead (r = -0.202, p = 0.283), and there was no correlation between blood lead and working time duration with hemoglobin and erythrocytes.